We are given a function of #x# that we must differentiate:
#f(x) = [x/(Sin x Cos x) ]# #color(red)(Function.1)#
#rArr f(x) = y = [x/(Sin x Cos x) ]#
We need to find the First Derivative of #f(x)#
By observing #f(x)# we know that we must use the Quotient Rule to differentiate .
Quotient Rule for finding the derivatives states that
#color(blue)((dy)/(dx)[f(x)/g(x)] = [(g(x)*f'(x) - f(x)*g'(x))/[g(x)]^2]#
Using the Quotient Rule, we can write our #color(red)(Function.1)# as
#=[d/(dx)[x]*[Cos x Sin x] -x*d/(dx) [ Cos x Sin x]]/[Cos x Sin x]^2#
Product Rule for finding the derivatives states that
#color(blue)((dy)/(dx)[f(x)*g(x)] = [(f'(x)*g(x) + f(x)*g'(x)]#
#=[1*[Cos x Sin x] -x*[d/(dx) [ Cos x]* Sin x+Cos x*d/(dx)[Sin x]]]/[Cos^2 x Sin^2 x]#
On simplification we get,
#=[[Cos x Sin x] -x[- Sin x* Sin x+Cos x Cos x]]/[Cos^2 x Sin^2 x]#
We can simplify further to get
#=[[Cos x Sin x] -x[- Sin^2 x+Cos^2 x]]/[Cos^2 x Sin^2 x]#
We can rearrange terms to get
#=[[Cos x Sin x] -x[Cos^2 x - Sin^2 x]]/[Cos^2 x Sin^2 x]#
We can simplify further to obtain
#=[Cos x Sin x]/[Cos^2 x Sin^2 x] -[x[Cos^2 x - Sin^2 x]]/[Cos^2 x Sin^2 x]#
We can rewrite the above expression as
#=[Cos x Sin x]/[[Cos x Sin x]*[Cos x Sin x]] -[x*Cos^2 x]/[Cos^2 x Sin^2 x] + [x*Sin^2 x]/[Cos^2 x Sin^2 x] #
We can now cancel terms as
#=[cancel(Cos x Sin x)]/[[cancel(Cos x Sin x)]*[Cos x Sin x]] -[x*cancel(Cos^2 x)]/[cancel(Cos^2 x) Sin^2 x] + [x*cancel(Sin^2 x)]/[Cos^2 x cancel(Sin^2 x)] #
In this step, we get
#1/(Cos x Sin x)-x/(Sin^2 x) + x/Cos^2 x# ....... Final Result
I hope you find this solution helpful.